Novel approach to fabricate porous sponges of poly(o,klactic-co-glycolic acid)without the use of organic solvents - Mooney, D.J.; Baldwin, D.F.; Suht, N.P.; Vacantis, J.P.; Larger, R.
A novel method was developed to produce highly porous sponges for potential use in tissue engineering, without the use of organic solvents. Highly porous sponges of biodegradable polymers are frequently utilized in tissue engineering both to transplant cells or growth factors, and to serve as a template for tissue regeneration. The processes utilized to fabricate sponges typically use organic solvents, but organic residues remaining in the sponges may be harmful to adherent cells, protein growth factors or nearby tissues. This report describes a technique to fabricate macroporous sponges from synthetic biodegradable polymers using high pressure carbon dioxide processing at room temperature. Solid discs of poly (D,L-lactic-co-glycolic acid)were saturated with COP by exposure to high pressure CO1 gas (5.5 MPa)for 72 h at room temperature. The solubility of the gas in the polymer was then rapidly decreased by reducing the CO* gas pressure to atmospheric levels. This created a thermodynamic instability for the CO2 dissolved in the polymer discs, and resulted in the nucleation and growth of gas cells within the polymer matrix. Polymer sponges with large pores (approximately 100 pm)and porosities of up to 93
Keywords: BIODEGRADABLE POLYMERS; CARBON DIOXIDE; MACROPORES; TISSUE ENGINEERING